Brief communication: Annual variability of the atmospheric circulation at large spatial scale reconstructed from a data assimilation framework cannot explain local East Antarctic ice rises' surface mass balance records - Cavitte, M. G. P.; Goosse, H.; Dalaiden, Q.; Ghilain, N. (The Cryosphere, 2025)
Ice cores are influenced by local processes that alter surface mass balance (SMB) records. To evaluate whether atmospheric circulation on large spatial scales explains the differing SMB trends at eight East Antarctic ice rises, we assimilated ice core SMB records within a high-resolution downscaled atmospheric model, while incorporating radar-derived SMB constraints to quantify local observation errors. The reconstruction captures the diverse variability from SMB records but may over-fit by introducing unrealistic wind spatial heterogeneity. While local errors are quantified, they might not cover all uncertainties. Moreover, small-scale wind circulation, unresolved in the reconstruction, could significantly affect local ice core SMB signals.
Keywords: Dronning Maud Land; iskjerner; klimamodeller; kryosfæren; meteorologi

Antarctic Water Stable Isotopes in the Global Atmospheric Model LMDZ6: From Climatology to Boundary Layer Processes - Dutrievoz, Niels; Agosta, Cécile; Risi, Camille; Vignon, Étienne; Nguyen, Sébastien; Landais, Amaëlle; Fourré, Elise; Leroy-Dos Santos, Christophe; Casado, Mathieu; Masson-Delmotte, Valérie; Jouzel, Jean; Dubos, Thomas; et al. (Journal of Geophysical Research: Atmospheres, 2025)
Observations of water stable isotopes in Antarctic surface snow, precipitation and water vapor are key for improving our understanding of the atmospheric water cycle and past climate reconstructions from ice cores. In this study, we use isotopic observations in Antarctica to assess the skill of the isotope-enabled atmospheric general circulation model LMDZ6, nudged to ERA5 above the boundary layer (1980?2023 period). The model has no significant bias for time-mean temperature and snow accumulation over the ice sheet. Sensitivity test on parameterized supersaturation strength highlights its opposite effect on precipitation ${δ }^{18}$O and d-excess. Selecting an intermediate supersaturation strength resulted in a minimal bias for surface snow ${δ }^{18}$O across the continent, with a reduced but systematic positive bias in surface snow d-excess ( ${\sim} $5?). We then assessed seasonal and diurnal isotope variability with daily precipitation and continuous vapor isotopes at Dumont d?Urville (DDU, coastal station) and Concordia (inland station). On a seasonal scale, LMDZ6iso accurately reproduces the seasonal cycle of precipitation ${δ }^{18}$O and d-excess at both stations. Moving from statistical evaluation to physical analysis, we use the individual process contributions to boundary-layer water vapor isotopes to identify the main drivers controlling the clear-sky isotopic daily cycles. At Concordia, daily isotope variations are mainly driven by surface sublimation, whereas at DDU they are driven by surface sublimation and advection by the katabatic flow. Our results suggest that to further improve water isotopes in LMDZ6iso, fractionation during surface sublimation should be included and fractionation at condensation for low temperature should be better constrained.
Keywords: Antarktis; global klimamodell; iskjerner; klimamodeller; klimatologi; meteorologi; paleoklimatologi; vannstabile isotoper

Microplastics in Southern Ocean sea ice: a pan-Antarctic perspective - Anna Kelly; Thomas Rodemann; Klaus M. Meiners; Heidi J. Auman; Sebastien Moreau; Francois Fripiat; Bruno Dellile; Delphine Lannuzel (Water Emerging Contaminants & Nanoplastics, 2024)
Microplastic (MP; plastic particles < 5 mm) pollution is pervasive in the marine environment, including remote polar environments. This study provides the first pan-Antarctic survey of MP pollution in Southern Ocean sea ice by analyzing sea ice cores from several diverse Antarctic regions. Abundance, chemical composition, and particle size data were obtained from 19 archived ice core samples. The cores were melted, filtered, and chemically analyzed using Fourier-transform infrared spectroscopy and 4,090 MP particles were identified. Nineteen polymer types were found across all samples, with an average concentration of 44.8 (± 50.9) particles·L-1. Abundance and composition varied with ice type and geographical location. Pack ice exhibited significantly higher particle concentrations than landfast ice, suggesting open ocean sources of pollution. Winter sea ice cores had significantly more MPs than spring and summer-drilled cores, suggesting ice formation processes play a role in particle incorporation. Smaller particles dominated across samples. Polyethylene (PE) and polypropylene (PP) were the most common polymers, mirroring those most identified across marine habitats. Higher average MP concentrations in developing sea ice during autumn and winter, contrasting lower levels observed in spring and summer, suggest turbulent conditions and faster growth rates are likely responsible for the increased incorporation of particles. Southern Ocean MP contamination likely stems from both local and distant sources. However, the circulation of deep waters and long-range transport likely contribute to the accumulation of MPs in regional gyres, coastlines, and their eventual incorporation into sea ice. Additionally, seasonal sea ice variations likely influence regional polymer compositions, reflecting the MP composition of the underlying waters.
Keywords: Sørishavet; forurensning; havis; iskjerner; mikroplast; sjøis

Hemispheric black carbon increase after the 13th-century Māori arrival in New Zealand - McConnell, Joseph R; Chellman, Nathan J; Mulvaney, Robert; Eckhardt, Sabine; Stohl, Andreas; Plunkett, Gill; Kipfstuhl, Sepp; Freitag, Johannes; Isaksson, Elisabeth; Gleason, Kelly E; Brugger, Sandra O; McWethy, David B; et al. (Nature, 2021)
New Zealand was among the last habitable places on earth to be colonized by humans. Charcoal records indicate that wildfires were rare prior to colonization and widespread following the 13th- to 14th-century Māori settlement, but the precise timing and magnitude of associated biomass-burning emissions are unknown, as are effects on light-absorbing black carbon aerosol concentrations over the pristine Southern Ocean and Antarctica. Here we used an array of well-dated Antarctic ice-core records to show that while black carbon deposition rates were stable over continental Antarctica during the past two millennia, they were approximately threefold higher over the northern Antarctic Peninsula during the past 700 years. Aerosol modelling demonstrates that the observed deposition could result only from increased emissions poleward of 40° S—implicating fires in Tasmania, New Zealand and Patagonia—but only New Zealand palaeofire records indicate coincident increases. Rapid deposition increases started in 1297 (±30 s.d.) in the northern Antarctic Peninsula, consistent with the late 13th-century Māori settlement and New Zealand black carbon emissions of 36 (±21 2 s.d.) Gg y−1 during peak deposition in the 16th century. While charcoal and pollen records suggest earlier, climate-modulated burning in Tasmania and southern Patagonia, deposition in Antarctica shows that black carbon emissions from burning in New Zealand dwarfed other preindustrial emissions in these regions during the past 2,000 years, providing clear evidence of large-scale environmental effects associated with early human activities across the remote Southern Hemisphere.
Keywords: Antarktis; iskjerner; miljø; paleoklimatologi

A Mobile, Multichannel, UWB Radar for Potential Ice Core Drill Site Identification in East Antarctica: Development and First Results - Rodriguez-Morales, Fernando; Braaten, David; Trong Mai, Hoang; Paden, John; Gogineni, Prasad; Yan, Jie-Bang; Abe-Ouchi, Ayako; Fujita, Shuji; Kawamura, Kenji; Tsutaki, Shun; Liefferinge, Brice Van; Matsuoka, Kenichi; et al. (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2020)
We developed a high-performance, multichannel, ultra-wideband radar system for measurements of the base and interior of the East Antarctic Ice Sheet. We designed the radar to be of high power (4000-W peak) yet portable and to be able to operate with 60-MHz bandwidth at a center frequency of 200 MHz, providing high sensitivity and fine vertical resolution relative to current technology. We used the radar to perform extensive measurements as a part of a multinational collaboration. We collected data onboard a tracked vehicle outfitted with an array of high-gain antennas. We sounded 2- to 3-km thick ice near Dome Fuji. Preliminary ice thickness data match those obtained via semicoincident measurements performed with a different surface-based pulse modulated radar system operated during the same field campaign, as well as previous airborne measurements. In addition, we mapped internal reflection horizons with fine vertical resolution from 300 m below the ice surface to ∼100 m above the bed. In this article, we provide a detailed overview of the radar instrument design, implementation, and field measurement setup. We present sample data to illustrate its capabilities and discuss how the data collected with it will be valuable for the assessment of promising drilling sites to recover ice cores that are 0.9–1.5 million years old.
Keywords: Antarktis; glasiologi; innlandsis; iskjerner

Snowfall and Water Stable Isotope Variability in East Antarctica Controlled by Warm Synoptic Events - Servettaz, Aymeric P M; Orsi, Anais J; Curran, Mark A J; Moy, Andrew D; Landais, Amaelle; Agosta, Cécile; Winton, V Holly L; Touzeau, Alexandra; McConnell, Joseph R; Werner, Martin; Baroni, Mélanie (Journal of Geophysical Research: Atmospheres, 2020)
Understanding climate proxy records that preserve physical characteristics of past climate is a prerequisite to reconstruct long-term climatic conditions. Water stable isotope ratios (δ18O) constitute a widely used proxy in ice cores to reconstruct temperature and climate. However, the original climate signal is altered between the formation of precipitation and the ice, especially in low-accumulation areas such as the East Antarctic Plateau. Atmospheric conditions under which the isotopic signal is acquired at Aurora Basin North (ABN), East Antarctica, are characterized with the regional atmospheric model Modèle Atmosphérique Régional (MAR). The model shows that 50% of the snow is accumulated in less than 24 days year−1. Snowfall occurs throughout the year and intensifies during winter, with 64% of total accumulation between April and September, leading to a cold bias of −0.86°C in temperatures above inversion compared to the annual mean of −29.7°C. Large snowfall events are associated with high-pressure systems forcing warm oceanic air masses toward the Antarctic interior, which causes a warm bias of +2.83°C. The temperature-δ18O relationship, assessed with the global atmospheric model ECHAM5-wiso, is primarily constrained by the winter variability, but the observed slope is valid year-round. Three snow δ18O records covering 2004–2014 indicate that the anomalies recorded in the ice core are attributable to the occurrence of warm winter storms bringing precipitation to ABN and support the interpretation of δ18O in this region as a marker of temperature changes related to large-scale atmospheric conditions, particularly blocking events and variations in the Southern Annular Mode.
Keywords: Antarktis; iskjerner; meteorologi; nedbør; paleoklimatologi; vannstabile isotoper